IMPLEMENTATION OF DEMONSTRATION METHOD BASED ON THE WORLDBOARD MEDIA TO IMPROVE SPIRITUAL AND MUSICAL INTELLIGENCE (Study in Group B PAUD PKK Talang Tinggi District of Seluma) - Saprida Sisanti; Alexon Alexon (DIADIK, 2018)
The purpose of the study was to describe the application of demonstration methods in improving spiritual and musical intelligence of early childhood based on joyful board media in group B in PKK talang Tinggi ECD Seluma District. This study used Clasroom Action Research (CAR). The subjects of this study were 15 children in  group B1 in PKK Talang Tinggi Seluma District. The data collection techniques used a child’s observation sheet on spiritual and musical intelligence. Analysis of  researcd  data  used mean and  T test. The results of  the study show  that children’s musicality  in  cycles 1,2  and 3. The results of  this  study  show  that teacher  has  successfully  implemented  this method, furthermore, this method can scientifically spiritual and musical intelligence. The results of this study recommend that joyful board media is one of the media that can be done by teachers to improve spiritual and musical intelligence